2019
DOI: 10.1002/da.22944
|View full text |Cite
|
Sign up to set email alerts
|

Mood and suicidality outcomes 3–11 years following pediatric anxiety disorder treatment

Abstract: Background Youth anxiety interventions have potential to reduce risk for depression and suicidality. Methods This naturalistic follow‐up of the multi‐site, comparative treatment trial, Child/Adolescent Anxiety Multimodal Study (CAMS), reports rates and predictors of mood disorders, suicidal thinking and behavior, and depressive symptoms 3–11 years (mean 6.25 years) following 12‐week evidence‐based youth anxiety treatment. Participants (N = 319; 10–26 years, mean 17 years) completed semiannual questionnaires an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…Moreover, their levels of depressive symptoms follow their levels of anxiety symptom subtypes and do not seem to be separate from the different anxiety symptom subtypes. This is in line with research indicating that anxiety is a predictor of depression ( 59 , 60 ). It may seem that those suffering from internalizing symptoms have overall high symptom levels across subtypes, also including depressive symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, their levels of depressive symptoms follow their levels of anxiety symptom subtypes and do not seem to be separate from the different anxiety symptom subtypes. This is in line with research indicating that anxiety is a predictor of depression ( 59 , 60 ). It may seem that those suffering from internalizing symptoms have overall high symptom levels across subtypes, also including depressive symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…Future LTFUs should emphasize recruitment and retention of more diverse populations, with a particular focus on the barriers that these populations face to participation in research more generally. 50 Finally, the predictive power of p should be examined alongside predictor variables other than those used here (eg, depression 51 ) and in relation to a broader set of outcomes, and by including variables that may mediate outcome (eg, interim negative life events). Furthermore, p may be reciprocally or causally related to some of the factors included as covariates in this study (eg, family and overall functioning).…”
Section: Discussionmentioning
confidence: 99%
“…There are often negative emotions, such as anxiety and depression caused by various reasons, for adolescent patients. [ 12 ] Some previous studies have reported the effect of preoperative anxiety and depression in patients with trigeminal neuralgia on the outcome of MVD, but no studies have been conducted on patients with HFS. [ 13 ] As a result, the current work was conducted to examine the roles of preoperative anxiety and depression in the postoperative outcomes of MVD among HFS adolescent patients.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, HFS patients undergoing MVD have worse outcomes than those in older patients, [11] and such a phenomenon is worth exploring. There are often negative emotions, such as anxiety and depression caused by various reasons, for adolescent patients [12] . Some previous studies have reported the effect of preoperative anxiety and depression in patients with trigeminal neuralgia on the outcome of MVD, but no studies have been conducted on patients with HFS [13] .…”
Section: Introductionmentioning
confidence: 99%